A Clinical and Radiographic Evaluation of Zirconia Dental Implants: 10-Year Follow-Up. (30th December 2021) - Borgonovo, Andrea Enrico; Ferrario, Susanna; Maiorana, Carlo; Vavassori, Virna; Censi, Rachele; Re, Dino
Abstract : Purpose . The aim is to evaluate the survival and success rates, as well as the marginal bone loss (MBL) and periodontal indexes, of zirconia implants with 10-year follow-up. Materials and Methods . 10 patients were selected and 26 one-piece zirconia implants were used for the rehabilitation of single tooth or partially edentulous ridge. After 10 years, a clinical-radiographic evaluation was performed in order to estimate peri-implant tissue health and marginal bone loss. Results . The survival and success rates were 100%. The average marginal bone loss from baseline to 120 months after surgery was 0.92 ± 0.97 mm. Conclusion . One-piece zirconia dental implants are characterised by high biocompatibility, low plaque adhesion, and absence of microgap that can be related to the clinical success of these implants.